Active generation of nanoholes in DNA origami scaffolds for programmed catalysis in nanocavities - Jianbang Wang (Nature Portfolio, 2019)
DNA origami provide scaffolds for spatial and temporal control of catalytic functions in confined nanocavities. Here the authors engineer nanoholes in DNA origami scaffolds.